Modification of qSOFA Increases Mortality Prediction Accuracy in Sepsis Patients - Gunawan, Erik Jaya; Siahaan, Salmon Charles Pardoman Tua; Idarto, Areta; Pribadi, Florence; Handayani, Lidya (Jurnal Kedokteran Brawijaya, 2024)
The Quick Sequential Organ Failure Assessment (qSOFA) is a simple parameter, however, its sensitivity as a mortality predictor is low. This study aimed to improve the predictor performance of qSOFA for in-hospital mortality. This study was a retrospective single-centered cohort using medical record data. This study included 150 patients aged 18-80 years old, who experienced sepsis and received ICU care between September 2021 and August 2022. qSOFA and modified ROX index (mROX) were calculated based on the most severe condition recorded in the emergency department (ED). Each variable's area under the receiver operating characteristic (AUROC) curve, sensitivity, and specificity were compared to predict in-hospital mortality. qSOFA scores ≥2 and mROX values ≤3.20 were independent factors that increased the risk of in-hospital mortality (OR 3.69 and 21.50; p 0.004 and 0.005, respectively). The combination of qSOFA scores ≥2 and mROX value ≤3.20 as in-hospital mortality predictors resulted in AUROC 0.791 with a sensitivity of 71.7% and specificity of 75.7%. The AUROC, sensitivity, and specificity of the combination of qSOFA and mROX were higher than qSOFA (0.766, 70.8%, 70.3%) or mROX (0.760, 68.1%, 67.6%) alone. In conclusion, the combination of qSOFA scores ≥2 and mROX values ≤3.20 increase the sensitivity and specificity for predicting in-hospital mortality in sepsis patients.